There is no 'universal' knowledge, intercultural collaboration is indispensable - Mato, Daniel Alejandro (2011)
Within some significant circles, where hegemonic representations of the idea of 'science' are produced, certain orientations of scientific research are carried out, and science and higher education policies are made and applied, references to the alleged existence of two kinds of knowledge, one of which would have 'universal' validity, and 'the other' (in fact the several others) would not, are frequent and do have crucial effects over our academic work. Although some outstanding authors within the very Western tradition have criticized from varied perspectives such universalist ambitions/assumptions, and although many colleagues have reached convergent conclusions from diverse kinds of practices and experiences, such hegemonic representations of the idea of science are still current. The acknowledgment of this situation calls for a deep debate. This article responds to such a purpose by attempting to integrate into the debate a reflection on the shortcomings of hegemonic academic knowledge to understand social processes profoundly marked by cultural differences, historical conflicts and inequalities, as well as significant perspectives formulated by some outstanding intellectuals who self-identify as indigenous, and the experiences of some indigenous intercultural universities from several Latin American countries.